Complete genome sequences of seven Vibrio cholerae phages isolated in China - Bhandare, Sudhakar G.; Warry, Andrew; Emes, Richard D.; Su, Jingliang; Barrow, Paul A.; Atterbury, Robert J. (American Society for Microbiology, 2017)
The complete genome sequences of seven closely related Vibrio cholerae phages isolated from environmental sites in southeastern China are reported here. Phages QH, CJY, H1, H2, H3, J2, and J3 are members of the Podoviridae family and are highly similar to the previously sequenced Vibrio phages VP2, VP5, and phiVC8.